Direct comparison of an ultrasensitive real-time PCR assay with droplet digital PCR for the detection of PIK3CA hotspot mutations in primary tumors, plasma cell-free DNA and paired CTC-derived gDNAs - Smilkou, Stavroula; Kaklamanis, Loukas; Balgouranidou, Ioanna; Linardou, Helena; Papatheodoridi, Alkistis Maria; Zagouri, Flora; Razis, Evangelia; Kakolyris, Stylianos; Psyrri, Amanda; Papadimitriou, Christos; Markou, Athina; Lianidou, Evi (Frontiers in Oncology, 2024)
IntroductionDetection of PIK3CA mutations in primary tumors and liquid biopsy samples is of increasing importance for treatment decisions and therapy resistance in many types of cancer. The aim of the present study was to directly compare the efficacy of a relatively inexpensive ultrasensitive real-time PCR with the well-established and highly sensitive technology of ddPCR for the detection of the three most common hotspot mutations of PIK3CA, in exons 9 and 20, that are all of clinical importance in various types of cancer.Patients and methodsWe analyzed 42 gDNAs from primary tumors (FFPEs), 29 plasma-cfDNA samples, and 29 paired CTC-derived gDNAs, all from patients with ER+ metastatic breast cancer, and plasma from 10 healthy donors. The same blood draws were used for CTC isolation using EpCAM beads for positive immunomagnetic enrichment. All FFPEs and plasma-cfDNA samples were analyzed in parallel for PIK3CA mutations by ultrasensitive real-time PCR assay and droplet digital PCR.ResultsIn gDNAs from FFPEs, using ultrasensitive real-time PCR, the p.E545K mutation was detected in 22/42(52.4%), and the p.E542K and p.H1047R mutations were detected in 14/42(33.3%) and 16/42(38.1%), respectively. Using ddPCR, the p.E545K mutation was detected in 22/42(52.4%), p.E542K in 17/42(40.5%), and p.H1047R in 19/42(45.2%) samples, revealing a concordance between the two methodologies of 81%, 78.6% and 78.6% for each mutation respectively. In plasma-cfDNA, using ultrasensitive real-time PCR, the p.E545K mutation was detected in 11/29(38%) and both p.E542K and p.H1047R mutations in 2/29(6.9%).In the same plasma-cfDNA samples using ddPCR, p.E545K was detected in 1/29(3.5%), p.E542K in 2/29(6.9%), and p.H1047R in 3/29(10.5%) samples, revealing a concordance of 65.5%,100% and 93.1% for each mutation respectively. In paired CTC-derived gDNAs p.E545K was detected in 11/29(38%), p.E542K in 3/29(10.3%), and p.H1047R in 7/29(24.1%) samples.ConclusionsThis low-cost, high-throughput and ultrasensitive real-time PCR assay provides accurate and specific detection of PIK3CA hotspot mutations in liquid biopsy samples and gives similar results to ddPCR. This assay can be performed in labs where digital PCR instrumentation is not available. In CTC-derived gDNA and paired plasma-cfDNA, PIK3CA mutations detected were not identical, revealing that CTC and plasma-cfDNA give complementary information.